ANALISA PEMANFAATAN APLIKASI GO-FOOD BAGI PENDAPATAN PEMILIK USAHA RUMAH MAKAN DI KELURAHAN SAWOJAJAR KOTA MALANG - Arum Indraswari; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2018)
The innovation of technology and information in economic sector is considered important. The presence of innovation may provide any significant development for any enterprise proper. One of the enterprises which is currently in high-demand is restaurant enterprise. The high level of people mobility and demand in time are two leading reasons which create big opportunity for restaurant entrepreneurs. This study is aimed to figure out influenced factors in term of benefits earned by restaurants enterprise owners in Sawojajar sub-district, Malang municipality. The data gathered in this current study were analyzed by employing multiple linear regression and tested by using Eviews software. The results have indicated that food price, order quantity and operational hours simultaneously have significant control toward restaurant owner benefits in Sawojajar sub-district, Malang municipality. On the other hand, Go-food application has an effect on differentiate significant number of income before and after using the application.Kata kunci :application go-food, income, benefit of restaurant,